(untitled) (Journal of the College of Basic Education, 2022)
This study aims at investigating the effect of Fishbowl Technique in teaching grammar. Grammar structures are not easy to master because of the diversity between the grammar systems of Arabic and English. Therefore, teachers should reflect deeply this aspect and should try hard to experiment new techniques that may prove effective to redress this problem which is highly documented in the literature of ELT. Jawad (2006:2) stresses this idea by stating that Iraqi EFL users can not differentiate between grammatical patterns. Hence, the Fishbowl Technique hoping to fill a gap in the domain of teaching English grammar. This indicates that fishbowl technique is more effective in teaching grammar.